Ainsley Harriott's all-new Meals in Minutes. - Harriott, Ainsley (London B.B.C books, 2005)
This all-new collection from Ainsley Harriott features 80 delicious recipes that are quick to prepare and guaranteed to inspire even the most time-challenged cook From the master of speedy cooking, simple recipe techniques and readily available ingredients help you magic up a host of delicious dishes
Include Colored Illustration, Indexes
Keywords: Quick and easy cooking -- Low-fat diet